2018
DOI: 10.1002/hyp.11417
|View full text |Cite
|
Sign up to set email alerts
|

Determining hydrological regimes in an agriculturally used tropical inland valley wetland in Central Uganda using soil moisture, groundwater, and digital elevation data

Abstract: Inadequate knowledge exists on the distribution of soil moisture and shallow groundwater in intensively cultivated inland valley wetlands in tropical environments, which are required for determining the hydrological regime. This study investigated the spatial and temporal variability of soil moisture along 4 hydrological positions segmented as riparian zone, valley bottom, fringe, and valley slope in an agriculturally used inland valley wetland in Central Uganda. The determined hydrological regimes of the defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…This development is triggered by several issues, such as increasing food demand caused by demographic growth, climate change, and degradation of upland soils. Unlike the uplands, wetlands hold potential for year-round harvest, due to their fertile soils with a balanced soil water availability throughout the year [5].…”
Section: Introductionmentioning
confidence: 99%
“…This development is triggered by several issues, such as increasing food demand caused by demographic growth, climate change, and degradation of upland soils. Unlike the uplands, wetlands hold potential for year-round harvest, due to their fertile soils with a balanced soil water availability throughout the year [5].…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of this study to previous works is the type of data (soil moisture content, depth to groundwater level, soil physical properties, leaf area index, and climatic data) used for model calibration and simulation of soil water dynamic and vertical fluxes. Many studies have described and explained the factors that influence soil water dynamics [6,37,38] and soil moisture retention [16,39,40] at the wetland-catchment scale in East Africa. However, these studies are tailored to inland valley wetlands, yet floodplain wetlands exhibit different hydrological behavior compared to the inland valley wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…These high inter-zonal differences in maize growth, biomass, and grain productivity were probably related to the variability in soil moisture and fertilizer-use efficiency along the slope of the inland valley. A related study [20] at the same experimental site showed that soil moisture was generally higher at the center of the inland valley and decreased up-slope toward the fringe position ( Figure 2). They also found that soils at the center remained saturated for a longer time following precipitation when compared to the fringe and middle positions probably due to the higher levels of silt and soil organic carbon.…”
Section: Effect Of Hydrological Positionmentioning
confidence: 81%
“…The hydrological positions/sites were separated from each other by 20 m wide strips of natural (indigenous) vegetation, which remained undisturbed throughout the duration of the experiments. In the Namulonge inland valley, loamy soils prevail, with a predominance of silty loam Gleysols [20]. Other physical soil properties varied across the hydrological positions.…”
Section: Description Of the Experimental Sitementioning
confidence: 99%
See 1 more Smart Citation